Is there any correlation between restriction fragment length polymorphism of the L-MYC gene and metastasis of human nonsmall cell lung cancer? - (:unkn) unknown (My University, 2002)
A potential molecular marker associated with cancer susceptibility as well as metastasis, prognosis and adverse survival, is the L-myc gene. The studies of lung cancer patients from different populations have yielded controversial results. We studied 64 nonsmall cell lung cancer (NSCLC) patients and 37 healthy controls of Turkish origin for L-myc gene polymorphism. Our aim was to test the hypothesis that there was association between L-myc S allele in NSCLC and predisposition to the disease and TNM stage indicating tumor size, node classification and metastasis. Polymerase chain reaction restriction fragment length polymorphism and agarose gel electrophoresis were used to determine the L-myc oncogene genotypes. We found no significant difference, both in the distribution of the LL, LS and SS genotypes and in the allelic frequencies, between the patient group and the control group; that is, the frequencies of L-myc alleles were, L and S, 0.59 and 0.41, 0.60 and 0.40, respectively. Our data between the patient group and the control group; that is, the frequencies of L-myc alleles were, L and S, 0.59 and 0.41, 0.60 and 0.40, respectively. Our data concerning age, sex, size of tumors, histological type of tumors showed no significant association with L-myc genotype. However, a higher frequency of L-myc S allele in the squamous cell carcinoma compared to other histological groups was found, although this difference was not statistically significant. No association was found between the L-myc RFLP and increased risk of metastasis either to the lymph nodes or to other organs. Our results suggested that L-myc gene polymorphism was not a suitable prognostic marker of metastatic development in Turkish NSCLC patients. © 2002 Elsevier Science Inc. All rights reserved.